A new pollen-derived microcarrier for pantoprazole delivery - Akyüz, Lalehan; Sargın, İdris; Kaya, Murat; Ceter, Talip; Akata, Ilgaz (Elsevier BV, 2017)
Plant-derived carriers have emerged as promising materials for drug encapsulation. Especially, sporopollenin microcapsules extracted from diverse pollen species have been proved to be effective drug carriers due to their biocompatibility, homogeneity in size, resistance to harsh chemical conditions and high thermal stability. Here in this study, sporopollenin microcapsules were isolated successfully from the pollens of a common tree (Corylus avellana, the European hazelnut) and used as a carrier for pantoprazole (PaNa) (a proton pump inhibitor). The drug entrapment efficiency was recorded as 29.81%. SEM micrographs clearly showed the drug was loaded into the microcapsules through the apertures of microcapsule and also some drugs were adsorbed on the surface of microcapsules. FT-IR spectra analysis confirmed the drug loading. Thermogravimetric analysis revealed that thermal stability of PaNa was enhanced by encapsulation. In vitro release studies showed that PaNa-loaded sporopollenin microcapsules exhibited better release performance than the control. C. avellana sporopollenin microcapsules can make an efficient carrier for delivery of PaNa.
Keywords: Drug Carriers; Proton Pump İnhibitor; Colon Delivery; Pyridinylmethylsulfinylbenzimidazoles; Kinetics; Corylus; Hazelnut Pollen; Delayed-Release; Pollen; Pantoprazole